2015
DOI: 10.1080/17542863.2015.1091486
|View full text |Cite
|
Sign up to set email alerts
|

Parenting styles and emerging adult drug use in Cebu, the Philippines

Abstract: Parenting style is a potent and malleable influence on emerging adult substance use. Most of the parenting-substance use literature has been conducted in Western populations and it is unknown whether findings are generalizable to other cultures and contexts. We extended the parenting-substance use literature to a cohort of emerging adults in the Philippines using the Cebu Longitudinal Health and Nutrition Survey. We assessed associations between mothers’ and fathers’ parenting styles (authoritative, permissive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Our finding that profiles of substance users differed for the males and females in our study is consistent with other research with Asian populations (Hock et al, 2016; Lee & Kim, 2017). Like Lee and Kim’s study (2017), our study found that more males than females were likely to land in substance user profiles greater than “low use.” In contrast to other research, however, both profiles for males and females evidenced a unique class of users (glue/over-the-counter medication users for females; poly drug users for males) that accounted for approximately one in seven high school students.…”
Section: Discussionsupporting
confidence: 93%
“…Our finding that profiles of substance users differed for the males and females in our study is consistent with other research with Asian populations (Hock et al, 2016; Lee & Kim, 2017). Like Lee and Kim’s study (2017), our study found that more males than females were likely to land in substance user profiles greater than “low use.” In contrast to other research, however, both profiles for males and females evidenced a unique class of users (glue/over-the-counter medication users for females; poly drug users for males) that accounted for approximately one in seven high school students.…”
Section: Discussionsupporting
confidence: 93%
“…While we did not find a significant association between paternal parenting style and emerging adult offspring depressive symptoms in this study, fathers' parenting style is likely still meaningful to other indices of adjustment in this population. In another study, we reported that neglectful fathering style was related to increased odds of sons' drug use (Hock et al, 2016). Future research on parenting styles and offspring mental health should further explore gender differences.…”
Section: Discussionmentioning
confidence: 81%
“…In the context of the Philippines, the family unit is highly valued and influential in young people's lives (Medina, 2001). Previous research in the Philippines has found that parenting styles predicted adolescent educational attainment (Hindin, 2005) and emerging adult substance use (Hock et al, 2016), and that problematic family dynamics (e.g., parental domestic violence) predicted adolescent depressive symptoms (Hindin & Gultiano, 2006). Hindin (2005) found that the permissive parenting style was the style most commonly reported in this cohort in the Philippines and that adolescent boys were more likely to complete secondary school if they had authoritative or permissive mothers than if they had authoritarian or neglectful mothers (Hindin, 2005).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…The data concurred with Enten and Golan [ 41 ] stating that dietary habits and body image are affected by parenting, familial milieu, parent–child bonding and communication. Haines et al [ 47 ] demonstrated a low association (AOR = 0.73, CI = 0.60–0.88) between highly functioning families and obesity among the children, and Hock et al [ 50 ] posited the father–youth bonding to be of utmost importance in shielding against substance abuse.…”
Section: Connecting the Dots Between Ineffective Parenting Styles Substance Abuse And Eating Disordersmentioning
confidence: 99%